The effect of humidity on the reproduction of Amblyomma variegatum (Fabricus, 1794) (Acarina: Ixodidae) (1991)
The effect of humidity on the reproduction of Amblyomma variegatum (fabricus,1794) (acarina:ixodidae) was studied using different humidity ranges at constant tempreture of 25 °C